Mining of Wheat Pm2 Alleles for Goal-Oriented Marker-Assisted Breeding - Yu, Ziyang; Xiao, Luning; Su, Fuyu; Liu, Wei; Luo, Fuyi; Han, Ran; Mu, Yanjun; Zhang, Wenjing; Wu, Liru; Liang, Xiao; Sun, Nina; Li, Linzhi; et al. (Frontiers in Plant Science, 2022)
Powdery mildew of wheat, caused by Blumeria graminis f. sp. tritici (Bgt), is a devastating disease that seriously reduces yield and quality worldwide. Utilization of plant resistance genes is an attractive and effective strategy for controlling this disease. Among the reported powdery mildew (Pm) resistance genes, Pm2 exhibits a diverse resistance spectrum among its multiple alleles. It has been widely used in China for resistance breeding for powdery mildew. To mine more Pm2 alleles and clarify their distribution, we screened 33 wheat cultivars/breeding lines carrying Pm2 alleles from 641 wheat genotypes using diagnostic and Pm2-linked markers. To further investigate the relationships within the Pm2 alleles, we compared their resistance spectra, polymorphism of marker alleles and gene sequences, and found that they have identical marker alleles and gene sequences but diverse resistance spectra. In addition, the diagnostic kompetitive allele-specific PCR (KASP) marker, YTU-KASP-Pm2, was developed and was shown to detect all the Pm2 alleles in the different genetic backgrounds. These findings provide valuable information for the distribution and rational use of Pm2 alleles, push forward their marker-assisted breeding (MAS), and hence improve the control of wheat powdery mildew.